Mental Health Nurse’s Exposure to Workplace Violence Leads to Job Stress, Which Leads to Reduced Professional Quality of Life - Itzhaki, Michal; Bluvstein, Irit; Peles Bortz, Anat; Kostistky, Hava; Bar Noy, Dor; Filshtinsky, Vivian; Theilla, Miriam (Frontiers in Psychiatry, 2018)
Professional quality of life (ProQOL) reflects how individuals feel about their work as helpers. Psychiatric ward nurses cope with significant psychological and physical challenges, including exposure to verbal and physical violence. This study was based on two aspects of ProQOL, the positive compassion satisfaction, and the negative compassion fatigue, with the aim of investigating the relation of ProQOL to job stress and violence exposure at a large mental health center. Data were collected from 114 mental health nurses (49/63 M/F) who completed a self administered questionnaire examining violence exposure, ProQOL, and job stress. The results showed that during the last year, almost all nurses (88.6%) experienced verbal violence, and more than half (56.1%) experienced physical violence. Only 2.6% experienced no violence. ProQOL was not associated with violence exposure but was reduced by work stress and by previous exposure to violence; nurses who perceived their work as more stressful had lower satisfaction from their work. In conclusion, although most mental health nurses are exposed to physical and verbal violence, their ProQOL is more related to job stress than to workplace violence. Hospital managements should conduct work stress reduction intervention programs and promote strategizes to reduce workplace violence. Further exploration of: (a) Factors affecting ProQOL and (b) The effect of violence coping workshops on ProQOL, is warranted.